Peran Kepala Sekolah Dalam Melaksanakan Fungsi Manajerial di SDN Ciomas 1Peran Kepala Sekolah Dalam Melaksanakan Fungsi Manajerial di SDN Ciomas 1 - Maswati Maswati (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2022)
The aims of this research are (1). To analyze and describe the principal's planning in carrying out managerial functions at SDN Ciomas 1, (2) To analyze and describe the implementation of the principal's work program in carrying out managerial functions at SDN Ciomas 1, (3) To analyze and describe the principal obstacles in planning and implementation of managerial functions at SDN Ciomas 1. The method used in this study is a qualitative descriptive method. Data collection techniques are using interviews, observation and documentation. The results of this study indicate that the planning carried out by the principal in carrying out his function as managerial at SDN Ciomas 1 has prepared a future activity plan of an organization which includes long-term, medium-term, short-term plans, activity plans, compiling work programs, planning improvement teacher performance and set targets to be achieved. The implementation of the principal's work program in carrying out managerial functions at SDN Ciomas 1, including; KBM management activities, student programs such as new student admissions, extracurricular activities, competitions up to the national level. Furthermore, the implementation of the program of activities for fostering educators and education staff, supervision activities, PR activities, etc. The school work program is in accordance with the academic calendar, and in accordance with the national standard 8 program. The principal obstacles in planning and implementing managerial functions at SDN Ciomas 1, the obstacles are in managing educators, one of which is in improving teacher performance, then the obstacles in managing facilities and infrastructure are the limited land and lack of funds, because the school has been built since ancient times dutch. Keywords : Roles, Headmaster, Managerial Function